2018
DOI: 10.12659/ajcr.911520
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Neurotoxicity in a Peritoneal Dialysis Patient: Report of a Case and Review of the Pharmacokinetics of Acyclovir

Abstract: Patient: Male, 80Final Diagnosis: Neurotoxicity due acyclovirSymptoms: Confusion • hallucinationMedication: AcyclovirClinical Procedure: —Specialty: NephrologyObjective:Unusual clinical courseBackground:The elderly population in the United States and the world is rapidly increasing. With aging, immunity and kidney function decrease, thus predisposing people to viral illnesses for which there is no effective prophylaxis. Herpes zoster afflicts the elderly and other immunocompromised patients, like those with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
1
20
0
6
Order By: Relevance
“…Valacyclovir-associated neurotoxicity usually occurs within 48-72 h of treatment start, and the symptoms can be gradually relieved after the drug is discontinued for 4-14 d (Table 1). For the patient in the present study, the time of onset and duration of symptoms were similar to those reported in literature[14,16-25] (Table 1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Valacyclovir-associated neurotoxicity usually occurs within 48-72 h of treatment start, and the symptoms can be gradually relieved after the drug is discontinued for 4-14 d (Table 1). For the patient in the present study, the time of onset and duration of symptoms were similar to those reported in literature[14,16-25] (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Since acyclovir is mainly cleared by the kidneys, it is a consensus to reduce its dose in patients with renal failure[25]. The dose is mainly determined by a combination of factors such as different methods of dialysis, residual renal function, hydration, and age.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety‐seven of those were included in the analysis, representing a total of 119 independent patients (Figure 1). The cases were extracted from 86 clinical cases 9‐35,37‐48,50‐54,56‐63,65‐71,73,75‐77,80‐83,85‐100,102,103 and 11 case series 36,49,55,64,72,74,78,79,84,101,113 . Figure 1 shows the case selection flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of acyclovir levels in plasma was requested in 53 cases (44.5%), with a mean of 17.2 mcg/ml ±25.3, and levels in CSF in 10 cases, 15,17,18,26,31,113 with a mean of 1.2 mcg/ml ±1.6. The CMMG metabolite was also obtained in 10 cases, 25,31,34,37,51,113 with 8 determinations in plasma, 8 in CSF and 1 in urine.…”
Section: Resultsmentioning
confidence: 99%
“…Other limitations related to the treatment with ACV also exist. For instance, oral intake of ACV has an absorption efficiency of only 15-30% (Bean, 1992), and previous reports indicated that senior patients that had renal problems could experience significant neurotoxicity, because they were not able to properly excrete this drug (Chau, 2018). Another important limitation associated to ACV is the ability of HSV-1 and HSV-2 to mutate and generate variants that are resistant to this drug by acquiring point mutations in the gene encoding for the viral thymidine kinase (TK), which decreases enzyme expression or modifies substrate specificity abrogating acyclovir phosphorylation, or by acquiring mutations in the gene encoding for the viral DNA polymerase (UL30), which may enable HSV-1 and HSV-2 to replicate in the presence of ACV (Reusser, 1996).…”
Section: Acyclovirmentioning
confidence: 99%